Atrial fibrillation in the elderly - Nantsupawat T. (2014)
Atrial fibrillation (AF) is the most common arrhythmia in older adults with a prevalence of 9 % in adults aged 80 years or older. AF patients have a five times greater risk of developing stroke than the general population. Using anticoagulants for stroke prevention in the elderly becomes a challenge because both stroke and bleeding complications increase with age. CHA2DS 2-VASc and HAS-BLED scores are currently used as stroke and bleeding risk evaluations. When the HAS-BLED score is 3 or higher, caution and efforts to correct reversible risk factors are advised. Regardless of the HAS-BLED score, warfarin or novel oral anticoagulants are a IIa recommendation for CHA 2DS2-VASc of 1, except for a score of 1 for females, and a IA recommendation for the score of 2 or higher. Aspirin is no longer recommended for AF thromboprophylaxis. In an elderly patient, lenient rate control is preferred over rhythm control owing to fewer adverse drugs effects and hospitalizations. When rhythm control is needed, dronedarone is a new antiarrhythmic drug that can be considered in patients who have paroxysmal AF and no history of heart failure. Although less efficacious than amiodarone, dronedarone has a fewer thyroid, neurologic, dermatologic, and ocular side effects than amiodarone. © 2013 Springer International Publishing Switzerland.